Eksistensi dan Kehujjahan Urf sebagai Sumber Istimbath Hukum - Lailita Fitriani; Luthfa Surya Anditya; Minahus Saniyyah; Nicken Nawang Sari; Iffatin Nur (Al Hikmah, 2021)
Abstract The science of Usul Fiqh developed along with the development of Islam to various areas in the Arabian Peninsula. Research by the Usul Fiqh, it is necessary because many cultures outside of the Arabian Peninsula, which are at odds with the local culture of the Arabian Peninsula. Of course, it is a requirement of local communities who do not know much about Islam. Therefore, the clergy continue to do a lot of efforts to resolve the various problems that exist. Where it is constituted by several methods for the formulation of Islamic law in addition to the "al-Quran", "Sunna", "Ijma’" and "Analogy" which has been agreed upon by both parties, namely al-urf. For Muslims, wherever they are, for the law of the provisions of the Quran and the Hadith of the Prophet is not violated, local customs can be declared valid. Legal ijtihadiyah derived from the "custom" and then set as Islamic law where if the "custom" is a source of that change, then the law ijtihadiyah will also change. The Compilation of Islamic Law contains a consideration of the customs law which is used as the legal basis that there was product fiqh of marital property which is distinct different with the corpus of jurisprudence outside Indonesia. The basic example is based on the reality if the law changes to suit the turn of time, place, and conditions. From here it looks that the nature of Islamic law that dynamic can be seen very clearly. Keywords : ‘urf, Islamic law, and ijtihad